Challenges in the design and operation of processes for catalytic fast pyrolysis of woody biomass. (May 2016) - Yildiz, Güray; Ronsse, Frederik; Duren, Ruben van; Prins, Wolter
Abstract: With respect to the application of upgraded oils derived from biomass materials, the goal is to produce either high yields of transportation fuel compounds ( e.g. aromatics, olefins) and specialty chemicals ( e.g. phenolics), or just a drop-in refinery feedstock to be blended with the feed streams of existing petroleum refineries. It has already been recognized in the early days of fast pyrolysis R&D that the application of catalysis could be of major importance in controlling the quality and chemical composition of bio-oil. For this purpose catalytic fast pyrolysis (CFP) of biomass, which is a single step process based on the use of heterogeneous catalysts in the fast pyrolysis process, can be put in service. While the literature on CFP of biomass – mainly focused on catalyst screening – is rapidly expanding, there is an urgent need for the translation of laboratory results to viable process concepts and pilot plant trials by addressing key issues like the most suitable processing mode, reactor technology, and the way of heat integration of the process. The present paper discusses the CFP of lignocellulosic biomass in a process oriented way that may initiate a useful process technology development in near future. The final goal is to come up with recommendations and suggestions on how to realize this technique at a commercial/industrial scale. That requires a better understanding of the precise effects of the essential process parameters ( e.g. processing mode; in - or ex situ ) and design elements ( e.g. reactor type, catalyst type) on one hand, and definitions and outcomes of possible obstacles ( e.g. successive regeneration of the catalyst, effect of biomass ash) on the other. In this paper, the efficient and economical use of the primary and secondary products, and the heat integration of the process is discussed. Moreover, some process alternatives for an efficient CFP operation are suggested.